Modus and Subtext: the Illusion of Identity - Matevosyan, Lianna (Bulletin of Yerevan University H: Russian Philology, 2021)
Modus and subtext are different categories. The value implied by speaker does not always correspond to the objective meaning of the utterance. “The value implied by speaker”, or hidden meaning, is realized through the intonation. Teachers should be aware of the difference between pragmatic and projective methods of communication for adequate delivering it to students. Projective text cannot be correctly interpreted without a good knowledge of the relevant culture.